Ingredients Management Application: Pembangunan Aplikasi Pengurusan Bahan bagi Mengelakkan Kerugian dan Pembaziran Peniaga Makanan dengan Berkesan - Hamzah, Nordyani; Abdul Hamid, Norhamreeza (Applied Information Technology And Computer Science, 2022)
Ingredients Management Application is an application to manage the ingredients used by Kedai Makan Omak Siti. This application is proposed to further increase the level of efficiency of users in managing the ingredients required by their business. There are several problems faced by Kedai Makan Omak Siti such as no record of daily expenses, users not use online methods, and food supply is not guaranteed. Thus, this project proposed an application to solve those problems. In addition, this application uses a prototype model to make it easier for developers to better understand the system requirements. Morover, JAVA programming language is utilised as a programming language. The application employed Android Studio as the application server and SQLite as the database. In turn, this application can be used by users who have small business. The application not only helps users in managing their ingredients, it is also easy to use because the system is a mobile application that can be accessed from their smartphone. Users will be more willing and sensitive to purchase and add the required amount of ingredients once recorded in the application. This application will reduce the likelihood for users to lose out because they only buy the materials they need as well as avoid wastage